(untitled) (Journal of International Studies, 2011)
English title: For the 90th anniversary of diplomatic relationships between Mongolia and Russia: Perspective of the bilateral cooperation among Mongolia and Russia and further development of multilateral cooperation of Shangai Cooperation Organization